Effect of different rejuvenators on the rheological properties of aged SBS modified bitumen in long term aging. (10th August 2019) - Cao, Zhilong; Chen, Meizhu; Liu, Zhaoyang; He, Bianyang; Yu, Jianying; Xue, Lihui
Highlights: The relationship between temperature and viscosity of rejuvenated binders can be described properly by Arrhenius formula. The viscoelastic properties and rheological models of rejuvenated binders were analyzed by self-developed rheometer. Cashew shell oil rejuvenated binders has the best low-temperature cracking resistance after PAV aging. Abstract: Large amount of waste asphalt mixture will be produced in the process of pavement renovation and maintenance, and the waste asphalt mixture recycling can be achieved through rejuvenation. In this paper, four rejuvenators (vacuum stream oil, cashew shell oil, corn oil and waste engine oil) with different chemical composition were selected to rejuvenate aged SBS modified bitumen (ASMB). The influence of different rejuvenators on the rheological properties of rejuvenated aged SBS modified bitumen before and after long term aging were systematically investigated. In addition, a self-developed rheometer was applied to establish the rheological model of all binders and quantitatively analyze the effect of rejuvenators on the viscoelastic properties of ASMB at different temperature before and after aging. The result indicates that the flow activation energy of binder have a sharply decease after rejuvenating, while the smallest flow activation energy increment 7.43 kJ/mol of cashew shell oil rejuvenated ASMB implies the smallest temperature sensitivity change after PAV aging. The higher crossover point of ASMB rejuvenated by vacuum stream oil with nonpolar alkanes and waste engine oil with strong polarity, suggesting their poor softening effect. While ASMB rejuvenated by cashew shell oil containing aromatic derivatives with weak polarity shows the highest loss tangent, indicating its largest improvement of viscous behavior of ASMB after rejuvenating. And the lowest rutting factor of cashew shell oil rejuvenated ASMB after PAV aging, implying its best anti-aging property. From the analysis of rheological model, it is found that cashew shell oil can hinder the translation of binder from viscous behavior to elastic behavior during the aging process.